PRINSIP MUSYAWARAH DALAM AL QUR’AN - Bustami Saladin (UIN Mataram, 2018)
This paper discusses the syûrâ in the Qur’an. Syrâr as a legal and political principle for humanity is understood that Islam considers it important to respect the majority opinion of people who are competent and have commendable integrity but are not justifed in violating the provisions of Allah SWT. The Qur’an considers the importance of community involvement in the problems faced in reality. The details of the pattern and the way it is submitted to each community because one community can be different from the other community in accordance with the context at hand